Individual and unit level insights from hospital staff ratings on structural empowerment, leadership-management performance, well-being, and quality of care - Karin Lundin; Maria Engström; Bernice Skytt; Annika Strömberg; Marit Silén (BMC, 2024)
Abstract Background Leadership and access to structural empowerment are known to influence the work life experiences of staff and quality of care. Knowledge about relationships between specific factors of structural empowerment, leadership and management, staff well-being and quality of care at both an individual and unit level is scarce. Aim To study the relationship between staff-rated access to empowering structures, leadership and management performance, well-being, and quality of care in hospital settings measured at the individual level and aggregated at the unit level. Methods A cross-sectional correlative design was applied. Questionnaire data from 331 randomized hospital nursing staff working at 38 units in 25 hospitals in Sweden were analyzed using bivariate correlations and general estimation equation (GEE) models. Results Results from the bivariate analysis of relationships confirmed earlier research. In the GEE models, some unexpected results were found and differences between the individual and unit levels. Adding management and leadership as independent factors in the second model showed few relationships of significance to the outcome variables. Conclusion Results confirm the importance of staff access to empowering structures in relation to well-being and quality of care. Differences and similarities were shown when studying these relationships at both the individual and unit level. The findings feature implications for hospital management to promote staff access to empowering structures. The findings provide information on how these structures relate to the individual and the unit; information that could be useful when planning or implementing strategies with the aim to promote staff well-being and care quality. The non-significant results for leadership and management in relation to staff outcomes in the GEE-models, raise questions for further research where a shift from individual to organizational focused performances within the field of leadership is implied.